Clinical Characteristics and Outcomes of Pediatric Diabetic Patients in Baghdad: A Cross-Sectional Study - Taha, Mohammed Abdulridha; Taatosh, Muntasser Nomas (American Journal of Biomedicine and Pharmacy, 2025)
Background: Diabetes mellitus in the pediatric population is a prominent health problem in Iraq and specific data on outcomes and clinical characteristics of pediatric diabetes in the location of Baghdad are scarce. Objective: To evaluate clinical characteristics, complications, and outcomes of pediatric diabetic patients admitted to Baghdad hospitals. Methods: A cross-sectional study of 485 diabetic patients (age 2-18) in three private hospitals in Baghdad was conducted from January 2024 - December 2024. Results: overall, 89.3% were Type 1 diabetes mellitus. The mean age of diagnosis was 8.4±3.2 years. Poor glycemic control (HbA1c >7.5%) occurred in 67.2% of patients, and 34.8% of patients had acute complications, most commonly diabetic ketoacidosis (18.6%). Conclusion: pediatric diabetes management in Baghdad faces high rates of poor glycemic control and acute complications. Enhanced diabetes care for Baghdad is needed.